THE INTERWOVEN OF STUDIES ON KNOWLEDGE, DISCIPLINES, AND TEXTBOOKS IN LATIN AMERICA: THE CASES OF BRAZIL, COLOMBIA, AND MEXICO - Martínez Moctezuma, Lucía; Martins, Maria do Carmo; Calderón Palacio, Isabel Cristina (Historia y Memoria de la Educación, 2024)
This article presents a balance of research on books, manuals, texts, knowledge, and school disciplines in Latin America, specifically in three Latin American countries, namely: Brazil, Colombia, and Mexico. From the event of the 30th anniversary of the Ibero-American Congress on the History of Education -CIHELA- where the investigations, objects of study and problematizations that, from the history of education, have been made in the region have been made visible. Through the analysis of documentary sources derived from the memories of CIHELA and other referents derived or connected with the Congress, a presentation of the contexts, developments and descriptions of each country is made, to conclude on the common points, the articulations, the differences in the approaches and routes of each country, as well as the challenges that are projected for research in this field in Latin America.